Long Mu Qing Xin mixture improves behavioral performance in spontaneously hypertensive rats (SHR/NCrl) by upregulating catecholamine neurotransmitters in prefrontal cortex and striatum via DRD1/cAMP/PKA-CREB signaling pathway - Li, Xuejun; Xiao, Zhen; Jiang, Zhiyan; Pu, Wenyan; Chen, Xiufeng; Wang, Shumin; Liu, Anqi; Zhang, Hongyu; Xu, Zihao (Frontiers in Pharmacology, 2024)
Background Attention deficit hyperactivity disorder (ADHD), a prevalent neurodevelopmental disorder in children, can be effectively alleviated by the herbal preparation Long Mu Qing Xin Mixture (LMQXM), but its mechanism has not been fully elucidated. Objective To scrutinize the potential pharmacological mechanisms by which LMQXM improves behavior in spontaneously hypertensive rats (SHR/NCrl). Methods The SHR/NCrl rats were randomly stratified into the model (SHR) group, the methylphenidate hydrochloride (MPH) group, and groups subjected to varying dosages of LMQXM into the medium dose (MD) group with a clinically effective dose, the low dose (LD) group with 0.5 times the clinically effective dose, and high dose (HD) group with 2 times the clinically effective dose. Furthermore, the WKY/NCrl rats constituted the control group. The evaluation of behavior involved the open field test and the Morris water maze test. HPLC, LC-MS, ELISA, immunohistochemistry, Western blot, and RT-qPCR were utilized to scrutinize the catecholamine neurotransmitter content and the expression of proteins and genes associated with the dopamine receptor D1 (DRD1)/cAMP/protein kinase A (PKA)-cAMP response element-binding (CREB) pathway in prefrontal cortex (PFC) and striatum. Results MPH and LMQXM ameliorated hyperactivity and learning and memory deficits of SHR/NCrl rats. Among them, LMQXM-MD and MPH also upregulated dopamine (DA), norepinephrine (NE), adenylate cyclase (AC) and cAMP levels, and the expression of proteins and genes associated with the DRD1/cAMP/PKA-CREB pathway in PFC and striatum of SHR/NCrl rats. PFC and striatum DA levels were also upregulated in the LMQXM-LD group as well as the striatum DA levels in the LMQXM-HD group, but there were no statistically significant differences in their NE levels compared to the SHR group. LMQXM-LD and LMQXM-HD also upregulated some DRD1/cAMP/PKA-CREB pathway-related proteins and gene expression, but the effects were discernibly disparate in PFC and striatum. Upon comprehensive analysis, LMQXM-MD appeared to be the most effective dose. Conclusion Our study tentatively suggests that LMQXM may rectify hyperactivity and learning and memory deficits of SHR/NCrl rats by elevating catecholamine neurotransmitters in the PFC and striatum. This effect may be attributed to the potential activation of the DRD1/cAMP/PKA-CREB signaling pathway, which appears to achieve an optimal response at moderate doses.